On the fast track: Driving down stunting in Vietnam - Keefe, Meagan (International Food Policy Research Institute, 2016)
VIETNAM HAS MADE dramatic progress in improving nutrition over the past three decades. Following the introduction of Vietnam’s Doi Moi (“renovation”) economic policies in 1986, the country’s economic performance began to improve rapidly. By the 1990s, Vietnam was among the fastest growing economies in the world. From one of the five poorest countries in the world in 1984, Vietnam rose to a rank of 167 out of 206 by 1999. As the country transitioned to a market-oriented economy, rapid economic growth was accompanied by a similarly dramatic decline in the poverty rate, which fell from nearly 75 percent of the population in 1984, to 58 percent in 1993, and down to 37 percent by 1998. Economic growth enabled the country to provide improved health services, which contributed directly to reductions in child malnutrition.